Artificial Intelligence and Administrative Law in Modern Governance - Yeri Antoni; Fatimah Nur Fauzia; Yovan Iristian (Faculty of Law, University of Dr. Soetomo, 2026)
This research examines the transformative impact of Artificial Intelligence (AI) and algorithmic decision-making (ADM) on administrative law and modern governance. As governments increasingly integrate AI into public services—from welfare distribution and tax administration to law enforcement—foundational principles of administrative law, including legality, transparency, and accountability, face unprecedented challenges. The objective of this study is to analyze how existing legal doctrines adapt to the